Missing pieces in decoding the brain oxytocin puzzle: Functional insights from mouse brain wiring diagrams - Manjila, Steffy B.; Betty, Rebecca; Kim, Yongsoo (Frontiers in Neuroscience, 2022)
The hypothalamic neuropeptide, oxytocin (Oxt), has been the focus of research for decades due to its effects on body physiology, neural circuits, and various behaviors. Oxt elicits a multitude of actions mainly through its receptor, the Oxt receptor (OxtR). Despite past research to understand the central projections of Oxt neurons and OxtR- coupled signaling pathways in different brain areas, it remains unclear how this nonapeptide exhibits such pleiotropic effects while integrating external and internal information. Most reviews in the field either focus on neuroanatomy of the Oxt-OxtR system, or on the functional effects of Oxt in specific brain areas. Here, we provide a review by integrating brain wide connectivity of Oxt neurons and their downstream circuits with OxtR expression in mice. We categorize Oxt connected brain regions into three functional modules that regulate the internal state, somatic visceral, and cognitive response. Each module contains three neural circuits that process distinct behavioral effects. Broad innervations on functional circuits (e.g., basal ganglia for motor behavior) enable Oxt signaling to exert coordinated modulation in functionally inter-connected circuits. Moreover, Oxt acts as a neuromodulator of neuromodulations to broadly control the overall state of the brain. Lastly, we discuss the mismatch between Oxt projections and OxtR expression across various regions of the mouse brain. In summary, this review brings forth functional circuit-based analysis of Oxt connectivity across the whole brain in light of Oxt release and OxtR expression and provides a perspective guide to future studies.